PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN IMPLEMENTASI E-COMMERCE TERHADAP KINERJA USAHA PELAKU UMKM DI DESA PENARUKAN - Masta Adi Putra, I Gusti Ngurah Putu; Pasek, Gede Widiadnyana (Komunitas Manajemen Kompetitif, 2024)
This research aims to determine the influence of entrepreneurial learning and the implementation of e-commerce on the business performance of MSMEs in Penarukan Village. The population in this research is all small business actors in Penarukan Village, totaling 74 small business actors. The sampling technique in this study used the Slovin formula so that the sample of respondents in this study was adjusted to 30, this was done to make data processing easier and for better test results. The data analysis method used to solve the problem in this research is multiple linear regression analysis which will be carried out using the SPSS (Statistics Program and Service Solution) program. Based on the results of the analysis, it is known that entrepreneurial learning has a positive effect on business performance and the implementation of e-commerce has a positive effect on business performance.